Presenting Four Learning Methods in Memorizing Al Qur'an at Syarifuddin Boarding School Lumajang, East Java - Syariful Himam; Asep Maulana (IJIE International Journal of Islamic Education, 2022)
Syarifuddin Islamic Boarding School Wonorejo Lumajang is one of the significant Islamic boarding schools in Lumajang, which can produce generations of memorizing the Qur'an with accountable reading quality. This is proven by the number of students who excel in the Musabaqoh Hifdzil Qur'an (MHQ) event at the district, provincial, and national levels and even being able to achieve at the ASEAN level. This study uses a type of field research with a descriptive qualitative approach. The selection of research subjects was carried out using a purposive technique. Data was collected through non-participant observation techniques, semi-structured interviews, and documentation. Meanwhile, the data obtained were analyzed through four data management activities guided by Miles and Huberman's procedures, including data collection, data condensation, data display, and conclusion drawing or verification. The research shows that implementing the memorization of al-Qur'an learning method to accelerate students' memorization applies four methods: the muroja'ah method, the kitabah method, the sima'i method, and the test method. The muroja'ah, the sima'i, and test methods were applied by all students who memorized the Qur'an, while the kitabah method was only used by students who followed bit-tartil level.